Mappings: shared histories ... a fragile self : September 1997 to January 1998 - Sood, Pooja (Eicher Gallery, 1997)
An exhibition by Indian and Pakistani artists, including Sikhs, Hindus and Muslims, of the Pakistani/ Indian experience
Catalog of exhibition held at the Eicher Gallery
Includes bibliographical references
Keywords: India; Pakistan; Ausstellungskatalog